Incidence of Poverty among Small-Scale Business Workers in the University of Lagos - Oluwaseyi Omowunmi Popogbe; Oluyemi Theophilus Adeosun (Unilag Journal of Humanities, 2022)
This study contributes to the discourse on poverty from a micro perspective by measuring poverty levels of business workers in the University of Lagos, Nigeria. Arguments by development economists are divided along the micro and macro dimensions of poverty, and evidence from countries like Nigeria shows that a growing economy does not translate to low poverty rates. Therefore, this paper examines the prevalence, depth and severity of poverty among small-scale business workers within the University of Lagos. With a population size of about 1260, 303 respondents were sampled for the study using a closed-ended questionnaire. Using the Foster, Greer and Thorbecke measurement technique, the researchers found that 69% of the respondents fell below the poverty line,while 40.84 and 5.51 were deemed to be in poverty depth and poverty severityrespectively. Their cost of basic needs was used as the approach in estimating the poverty line and was ₦1,008.68. Many of the respondents were below 25 years, single and still dependent on external sources for sustenance. Low income was a major reason for the poverty in this environment, not necessarily access to basic needs like water and accommodation. It is recommended that business workers acquire a skill that will make them more marketable and productive.